Comparison Of Students' Analitical Abilities In Learning Geography Using Models Problem Solving And Problem Posing at SMAN 1 Salimpaung - Fiqri, Muhammad Arrayyan; Tanamir, Momon Dt; Afryansih, Nila (Universitas Lampung, 2023)
This research aims to see a comparison of the analytical abilities of students in class X using problem solving and problem posing learning models. The research method uses quantitative descriptive. The type of research used is quasi experimental research. Based on the research results, it was found that the comparison of the analytical abilities of students in the experimental class 1 class obtained an average of 75.76, experimental 2 obtained an average of 80.47, while the control class obtained an average of 71.41. Based on the results of the hypothesis that has been carried out, it is found that the Sig of experiment class 1 and control is .019, experiment 2 and control is .000 and experiment 1 and experiment 2 is .009 which is <0.05 which is significant which means H0 is rejected and Ha is accepted. From these three classes, it can be concluded that there is a comparison of students' analytical abilities where the problem posing learning model has a higher average than the problem solving learning model.